ULTRA FAST EVOLUTION OF SAKURAI’s OBJECT - Pavlenko, Ya. (Одеські астрономічні публікації, 2017)
We model theoretical spectral energy distributions of the "born-again" V4334 Sgr for our grid of hydrogen-deficient model atmospheres with a range of Teff = 4000-5000 K and log g = 1.0 - 0.0. These SED’s are compared with the observed in 1997- 1998 spectra of V4334 Sgr. In that way we determine Teff of Sakurai’s object for the years, and parameters of interstellar + circumstellar reddening in the frame of self-consistent approach.